PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA CAJA DE AHORRO PARA LA ASOCIACIÓN DE AGENTES CIVILES DE TRÁNSITO DEL CANTÓN LOJA - Sánchez Pinta, Karina Paola (2019)
This research work consisted of conducting a study of the possibility of implementing a Savings Fund for the Association of Civil Transit Agents of the Canton Loja, which aims to foster a culture of saving and facilitate credit financing, in order to improve the socio-economic development and quality of life of each of them. For the research development the methods were used: deductive, inductive, statistical and analytical, as well as techniques such as observation, bibliographic collection and a survey the same that was applied to the 130 Civil Transit Agents in this way obtain relevant data to carry out subsequent studies. Thus, with the information obtained from the survey proceeded to develop the market study where the potential, real and effective demand of the project was determined, in order to justify the implementation of the savings bank. Similarly, to meet the second objective in relation to technical feasibility, the installed capacity, used and the location of the savings bank was established, describing through flowcharts the processes of the services that the financial institution. The legal administrative study took into account the legal basis applicable to this entity, determining the organizational structure of the savings bank, for a better provision of the service, thus designing a function manual for the different the departments that will make up the entity. Finally, through the financial study, the value of the total investment, the income and expenses needed to structure the flow of cash could be known, information that served to assess the feasibility of the project by means of indicators Net Current Value obtaining a result of $15,138.79, the Internal Rate of Return with a value of 37.40% being greater than the TMAR of 6.83%; Profit Ratio Cost of $1.20 which shows that for every dollar invested you will get a profit of $0.20 ctvs.; and in the Period of Recovery of Investment will recover in 3 years, 3 months and 2 days approximately. On this basis it is determined that it is advisable to implement the Savings Fund for the Association of Civil Transit Agents, for the favorable results obtained with which it is shown that the project will be sustainable in time and the proposal is technical feasible, financially, benefiting partners from fostering a culture of savings.